Can Table Tennis Extend Lifespan? An Analysis of Its Impact on Physical Health, Brain Function, and Mental Well-being - Patrycja Marta; Agata Ossolińska; Filip Huzarski; Gabriela Ferfecka; Klaudia Pawełek; Lucyna Stolarska; Magdalena Rosa-Bończak; Natalia Morawiecka; Olivier Carlton; Weronika Kłosowicz (Journal of Education, Health and Sport)
Introduction: In the context of an aging society, the importance of physical activity as a key element in supporting health and improving quality of life is growing. Table tennis, a sport played by millions worldwide, combines aerobic, coordination, and strategic exercises, making it unique in terms of its impact on physical and mental health.